Global energy dilemmas : energy security, globalization, and climate change - Bradshaw, Michael J. (Cambridge : Polity, 2014)
Today's global energy system faces two major challenges: how to secure the supply of reliable and affordable energy; and how to rapidly transform to a low-carbon, efficient, and environmentally harmless energy supply. This book explores the key aspects of the current global energy dilemma and examines how it is playing out across the major regions and countries of the world.--
Includes bibliographical references and index.
Keywords: Power resources; Energy policy; Power resources -- Economic aspects; Power resources -- Environmental aspects